Doktrin Manusia dan Dosa - Amanda Serafy Lumanauw; Hellen Candana Putri; Sarmauli Sarmauli (Lumen: Jurnal Pendidikan Agama Katekese dan Pastoral, 2024)
The doctrine of humans and sin from a Christian theological perspective emphasizes that humans are created in the image of God, with free will and moral responsibility. However, through the fall into sin, humans experience separation from God and damage to relationships with others and creation. Sin is understood as a violation of God’s law, resulting in spiritual and physical death. This research explores the concept of original sin inherited from Adam and Eve as well as sinful acts committed by individuals. By referring to the Bible and theological views from various sources, this research provides an understanding of the importance of sin in human life and efforts to restore relationships through God’s grace.